The seroprevalence of COVID-19 in patients living with HIV in metropolitan Detroit. (May 2022) - Gudipati, Smitha; Lee, Monica; Scott, Megan; Yaphe, Sean; Huisting, Joanne; Yared, Nicholas; Brar, Indira; Markowitz, Norman
Background: COVID-19, a novel respiratory illness caused by SARS-CoV-2, has become a global pandemic. As of December 2020, 4.8% of the 941 people living with HIV in our Ryan White clinic have tested polymerase chain reaction positive for SARS-CoV-2. The aim of our study was to estimate the seroprevalence of COVID-19 in our Ryan White people living with HIV, irrespective of known past infection. Methods: We conducted a cross-sectional study that recruited people living with HIV in the Ryan White program at Henry Ford Hospital in Detroit, Michigan, from September 2020 through May 2021. All Ryan White patients were offered participation during clinic visits. After informed consent, patients completed a survey, and had blood sampled for SARS-CoV-2 antibody testing. Results: Of the 529 individuals who completed the written survey, 504 participants were tested for SARS-CoV-2 antibody and 52 people living with HIV were COVID-19 immunoglobulin (Ig) G positive resulting in a seroprevalence of 10.3%. Among 36 persons with PCR-confirmed COVID-19, 52.8% were IgG negative. Inclusion of PCR positive but IgG-negative people living with HIV yields a COVID-19 infection prevalence of 14.1%. Conclusions: These findings suggest that passive public health-based antibody surveillance in people living with HIV significantly underestimates past infection.